Quantity, quality, and functionality of peripheral blood cells derived from residual blood of different apheresis kits. Issue 6 (6th May 2018) - Knörck, Arne; Marx, Stefanie; Friedmann, Kim S.; Zöphel, Sylvia; Lieblang, Lisa; Hässig, Carmen; Müller, Isabelle; Pilch, Jan; Sester, Urban; Hoth, Markus; Eichler, Hermann; Sester, Martina; et al.
Abstract : BACKGROUND: Research with primary human white blood cell (WBC) subpopulations requires high quantity, quality, and functionality of peripheral blood mononuclear cells (PBMCs) as a source to further characterize cellular subpopulations such as T and B lymphocytes, monocytes, or natural killer cells. Apart from buffy coats derived from whole blood, residual blood from preparative hemapheresis kits are used as a source for PBMCs, but knowledge on the yield and functionality of cells from different devices is limited. STUDY DESIGN AND METHODS: We evaluated quantity and quality of PBMCs isolated from apheresis kits of two apheresis devices (AMICUS, Fenwal; and Trima Accel, Terumo BCT), the latter being our standard source for many years. PBMCs derived from Trima or AMICUS were tested for yield and subtype composition by flow cytometry. Functionality was assessed by cytokine induction of CD4 + and CD8 + T cells and by degranulation. Moreover, cytotoxic activity of natural killer cells was quantified by a real‐time killing assay. RESULTS: Mean numbers of isolated cells were 5.5 ± 2.4 × 10 8 for AMICUS, and 10.3 ± 6.4 × 10 8 for Trima Accel, respectively. The proportion of WBC subtypes corresponded to well‐known numbers from whole blood, with minor differences between the two apheresis systems. Likewise, minor differences in cytokine induction were found in stimulated CD4 + or CD8 + T cells. Finally, PBMCs derived from the two systems showed comparable cytotoxic activity. CONCLUSION: PBMC derived from residual blood of the AMICUS and Trima Accel apheresis devices serve as an economic and easily accessible source for functional PBMCs with comparable quantity and quality to PBMCs derived from whole blood.